2001
DOI: 10.1103/physrevlett.87.156103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Scale Density Oscillations in Water Adjacent to a Mica Surface

Abstract: High-resolution specular x-ray reflectivity of the mica(001)-water interface under ambient conditions reveals oscillations in water oxygen density in the surface-normal direction, giving evidence of interfacial water ordering. The spacings between neighboring water layers in the near-surface, strongly oscillatory region are 2.5(2)-2.7(2) A, approximately the size of the water molecule. The density oscillations extend to about 10 A above the surface and do not strictly maintain a solvent-size periodicity as tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

105
535
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(648 citation statements)
references
References 32 publications
105
535
8
Order By: Relevance
“…The picture that emerges from these studies matches well with previous experimental and computational studies. In particular, by using a direct measurement of the nanomechanics of the system, we confirm the existence of the adsorbed water layer on mica surface as suggestedby earlier studies [29,30]. By analyzing the data using two different viscoelastic models, using improved data analysis methods to determine the true tipsurface separation, and determining the film stiffness in two distinct ways, we reconstructed the overall dynamics and viscoelastic response as a hydration layer is rapidly compressed and expelled between two approaching hydrophilic surfaces.…”
Section: Resultssupporting
confidence: 76%
“…The picture that emerges from these studies matches well with previous experimental and computational studies. In particular, by using a direct measurement of the nanomechanics of the system, we confirm the existence of the adsorbed water layer on mica surface as suggestedby earlier studies [29,30]. By analyzing the data using two different viscoelastic models, using improved data analysis methods to determine the true tipsurface separation, and determining the film stiffness in two distinct ways, we reconstructed the overall dynamics and viscoelastic response as a hydration layer is rapidly compressed and expelled between two approaching hydrophilic surfaces.…”
Section: Resultssupporting
confidence: 76%
“…Therefore, the results obtained in this study support the model proposed by Cheng et al [93], where the adsorbed and laterally-distributed water molecules coexists at the interface. The co-existence of water molecules having a long relaxation time (adsorbed water) and laterally-distributed disordered water molecules (2D hydration layer) may reconcile the two opposing ideas of "ice-like" and "liquid-like" water molecules at the mica-water interface.…”
Section: Mica-water Interfacesupporting
confidence: 91%
“…In addition, owing to the ease of cleavage to present an atomically flat surface, mica-water interface has been widely used as a model system to investigate nanofluidics in engineering and physics [87], lubrication in tribology, and molecular adsorption and diffusion in biology and chemistry. To date, water distribution at mica-water interface has been extensively studied by various techniques [88][89][90][91][92][93][94]. However, its atomistic model has not been established due to the difficulties in visualizing molecular-scale water distribution directly at a solid-liquid interface.…”
Section: Mica-water Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Huisman et al 4 found evidence for layering of liquid gallium in contact with a diamond surface using x-ray diffraction. Recently Cheng et al 5 found molecular-scale density oscillation at the water/ mica interface using specular reflectivity.…”
mentioning
confidence: 99%